2020
DOI: 10.1155/2020/8850926
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Curcumin Gel on Zinc, Magnesium, Copper, IL‐1β, and TNF‐α in Chronic Periodontitis Patients

Abstract: Curcumin exhibits antibacterial, antioxidant, and anti-inflammatory effects and has been suggested as a treatment for inflammatory diseases. The study is aimed at evaluating the effect of curcumin gel on serum levels of micronutrients (zinc, copper, and magnesium) and proinflammatory cytokines (IL-1β and TNF-α) in chronic periodontitis patients. Ninety subjects with an age of 25-54 were included in this study. From the total number, 30 subjects with healthy periodontium (control group) ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…From the 499 potentially relevant reports identified, 37 studies proved potentially eligible after title and abstract screening. Following full text screening, 18 RCTs ( Behal et al, 2011 ; Gottumukkala et al, 2013 ; Muglikar et al, 2013 ; Bhatia et al, 2014 ; Jaswal et al, 2014 ; Anuradha et al, 2015 ; Sreedhar et al, 2015 ; Arunachalam et al, 2017 ; Chatterjee et al, 2017 ; Singh et al, 2018 ; Jalaluddin et al, 2019 ; Kaur et al, 2019 ; Raghava et al, 2019 ; Guru et al, 2020 ; Mohammad, 2020 ; Pandey et al, 2021 ; Pérez-Pacheco et al, 2021 ; Rahalkar et al, 2021 ) involving 846 patients/sites were included in this meta-analysis. Table 1 displays the main characteristics of the 18 included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the 499 potentially relevant reports identified, 37 studies proved potentially eligible after title and abstract screening. Following full text screening, 18 RCTs ( Behal et al, 2011 ; Gottumukkala et al, 2013 ; Muglikar et al, 2013 ; Bhatia et al, 2014 ; Jaswal et al, 2014 ; Anuradha et al, 2015 ; Sreedhar et al, 2015 ; Arunachalam et al, 2017 ; Chatterjee et al, 2017 ; Singh et al, 2018 ; Jalaluddin et al, 2019 ; Kaur et al, 2019 ; Raghava et al, 2019 ; Guru et al, 2020 ; Mohammad, 2020 ; Pandey et al, 2021 ; Pérez-Pacheco et al, 2021 ; Rahalkar et al, 2021 ) involving 846 patients/sites were included in this meta-analysis. Table 1 displays the main characteristics of the 18 included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies ( Gottumukkala et al, 2013 ; Singh et al, 2018 ; Guru et al, 2020 ; Pandey et al, 2021 ; Pérez-Pacheco et al, 2021 ) mentioned allocation concealment. Participants and trial staff were not blinded in one study ( Jalaluddin et al, 2019 ), and 13 other studies ( Behal et al, 2011 ; Gottumukkala et al, 2013 ; Muglikar et al, 2013 ; Bhatia et al, 2014 ; Jaswal et al, 2014 ; Anuradha et al, 2015 ; Sreedhar et al, 2015 ; Arunachalam et al, 2017 ; Singh et al, 2018 ; Raghava et al, 2019 ; Mohammad, 2020 ; Pandey et al, 2021 ; Rahalkar et al, 2021 ) failed to mention blinding of participants and personnel. Only four studies ( Muglikar et al, 2013 ; Sreedhar et al, 2015 ; Kaur et al, 2019 ; Pérez-Pacheco et al, 2021 ) that reported outcome assessors were blinded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, serum concentrations of IL-1β, TNF-α and IL-17 showed a slight tendency to decrease (p>0.05). Previous studies that assessed clinical periodontal parameters and biomarkers in serum, before and after NSPT evidenced improvement in clinical parameters and diminished IL-1β, TNF-α and IL-17 levels in normosystemic patients with periodontitis [32,33].…”
Section: Discussionmentioning
confidence: 99%